2022
DOI: 10.3390/cells11244035
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Vimentin-Induced Disruption of Cell–Cell Associations Augments Breast Cancer Cell Migration

Abstract: In advanced metastatic cancers with reduced patient survival and poor prognosis, expression of vimentin, a type III intermediate filament protein is frequently observed. Vimentin appears to suppress epithelial characteristics and augments cell migration but the molecular basis for these changes is not well understood. Here, we have ectopically expressed vimentin in MCF-7 and investigated its genomic and functional implications. Vimentin changed the cell shape by decreasing major axis, major axis angle and incr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…KRT8 serves as an upstream regulatory gene in numerous signaling pathways associated with tumorigenesis, exhibiting abnormal expression in various epithelial-origin tumors such as breast cancer, gastric cancer, and pancreatic cancer [15][16][17] .The regulation of KRT8 is mediated by the MEK-ERK signaling pathway 18 . Busch et al have reported that the recombination process of cytokeratin and the metastasis of epithelial tumor cells are in uenced by KRT8 phosphorylation 19 .…”
Section: Discussionmentioning
confidence: 99%
“…KRT8 serves as an upstream regulatory gene in numerous signaling pathways associated with tumorigenesis, exhibiting abnormal expression in various epithelial-origin tumors such as breast cancer, gastric cancer, and pancreatic cancer [15][16][17] .The regulation of KRT8 is mediated by the MEK-ERK signaling pathway 18 . Busch et al have reported that the recombination process of cytokeratin and the metastasis of epithelial tumor cells are in uenced by KRT8 phosphorylation 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The mutagenized cDNA from the pBluescript vector is excised out and ligated into an expression vector such as pLPCpuro or pLPChygro in identical restriction sites, usually EcoRI and BamHI [9,10], and used for maxi DNA prep. These constructs can be used for protein expression by western blotting and immunostaining and can be employed for functional analysis.…”
Section: Sub-cloning Into An Expression Vectormentioning
confidence: 99%